Occurrence of myocardial bridges in Gir, Guzerá, Nelore and Indubrasil bovines - Severino, Renato Souto; Bombonato, Pedro Primo (Brazilian Journal of Veterinary Research and Animal Science, 1992)
One hundred hearts of adult Bos indicus, 68 males and 32 females of the Gir, Guzerá, Indubrasil and Nelore breeds were studied, to observe the frequency, width and localization of the myocardial bridges on the coronary arteries. The results permit the following conclusions: 1) myocardial bridges occur in 94.0% of the hearts in nunber between one to seven; 2) the width of the myocardial bridges varied from 0.1 an to 5.7 cm width a mean of 1.33 cm; 3) myocardial bridges occur width more frequency on the left coronary arteries branches (85.38%), than on the following right coronary arteries branches (14.62%).